Pollock - Brant, Peter M.; Allen, Joseph; Harris, Ed 1950-.; Berner, Fred. ([United States] Pollock Film, 2000)
A movie about the life and death of American painter Jackson Pollock, focusing on his works and life with Lee Krasner in the 1940s.
Disc 1: 1 hr., 3 min. -- disc 2: 1 hr.
Based on the book "Jackson Pollock : an American saga" by Steven Naifeh and Gregory White Smith.
VCD.
Screenplay by Barbara Turner and Susan J. Emshwiller ; directed by Ed Harris ; produced by Fred Berner, Ed Harris, Jon Kilik ; producer, James Francis Trezza
Ed Harris, Marcia Gay Harden, Tom Bower, Jennifer Connelly, Bud Cort.
Academy Awards, 2001: Best Actress in a Supporting Role (Marcia Gay Harden)
Keywords: Pollock, Jackson -- 1912-1956.; Krasner, Lee -- 1908-.; Painters -- United States -- Biography; Feature films